Discernment on assistive technology for the care and support requirements of older adults and differently-abled individuals - Muthu, P.; Tan, Yongqi; Latha, S.; Dhanalakshmi, Samiappan; Lai, Khin Wee; Wu, Xiang (Frontiers in Public Health, 2023)
Assistive technology for differently abled and elderly people has made remarkable achievements in providing rehabilitative, adaptive and assistive devices. The technology provides huge assistance for people with physical impairments to lead a better self-reliant daily life, in terms of mobility, education, rehabilitation etc. This technology ranges from simple hand-held devices to complex robotic accessories which promote the individual’s independence. This study aimed at identifying the assistance required by the impaired individual, the solutions proposed by different researchers and featured their merits and demerits. It gives detailed discussion on the state of art assistive technologies, their applications, challenges, types and their usage for rehabilitation. The work also tries to bring out the different unexplored research areas that are available in assistive technology, which will improve the daily life of the individuals and can advance the field. Despite assistive technologies provides high levels of usage, some limitations have been briefly described in the study. Hence, this review can help understand the utilization, pros and cons of assistive devices in rehabilitation engineering and assistive technologies.